Developing a guide for sustainable healthcare practice: A case study from the Swedish Society of Medicine - Andreas Vilhelmsson; Ida Persson Cofina; Maria Wolodarski; Tobias Alfvén (The Journal of Climate Change and Health)
Introduction: Although climate change has been consistently identified as one of the greatest threats to humans, many clinicians do not feel prepared to address climate change with patients and medical school curricula still have very little coverage of its health consequences. At the same time, health care providers have been shown to be trusted voices and are therefore well suited to help build the public and political necessary to enact policies that effectively address climate change and protect human health in equitable ways. Nevertheless, teaching climate, health and sustainable healthcare to medical colleagues, students and healthcare leaders can be challenging for various reasons. It is therefore essential to provide health care providers and leaders with the appropriate tools and communication skills to facilitate a more sustainable and greener healthcare. Case presentation: In this case report, we describe how we developed a sustainability guide for clinicians with examples of how to reduce unnecessary environmental and climate impact, without compromising patient safety, highlighting potential co-benefits for public health, healthcare efficiency, financial aspects and to the occupational environment. Discussion: The sustainability guide has been appreciated by medical specialties as a tool to illustrate concrete ways of working with sustainable healthcare in Sweden. It has also been used to introduce the field into the medical curriculum at Swedish universities and teach students in sustainability. Conclusion: Our sustainability guide highlights the potential value of providing health care personnel and leaders with the appropriate tools and communication skills to facilitate a more sustainable and green healthcare.